(untitled) (Third Sector Social Economic Review, 2020)
One of the macroeconomic investment theories, used to explain investment behavior in economics is the theory, known as the q theory of investments or Tobin’s q theory. In this study, it has been tried to determine whether new housing investments in Turkey is changed according to the Tobin’s q theory. The sensitivity of new housing investments to q ratios is analyzed by elasticity analysis. Results of the analysis show that 1% increase in the q ratio; increases the housing investments by 1.1488% in Istanbul, increases by 0.6984% in Izmir and increases by 1.0926% in Turkey, but, decreases the housing investments by 0.5149% in Ankara. It can be said that housing investments for Turkey, Istanbul and Izmir are sensitive to the q ratio, but for Ankara, housing investments are sensitive to the factors other than profitability.